Transcriptional versus metabolic control of cell fitness during cell competition. (June 2020) - Lawlor, Katerina; Pérez-Montero, Salvador; Lima, Ana; Rodríguez, Tristan A.
Abstract: The maintenance of tissue homeostasis and health relies on the efficient removal of damaged or otherwise suboptimal cells. One way this is achieved is through cell competition, a fitness quality control mechanism that eliminates cells that are less fit than their neighbours. Through this process, cell competition has been shown to play diverse roles in development and in the adult, including in homeostasis and tumour suppression. However, over the last few years it has also become apparent that certain oncogenic mutations can provide cells with a competitive advantage that promotes their expansion via the elimination of surrounding wild-type cells. Thus, understanding how this process is initiated and regulated will provide important insights with relevance to a number of different research areas. A key question in cell competition is what determines the competitive fitness of a cell. Here, we will review what is known about this question by focussing on two non-mutually exclusive possibilities; first, that the activity of a subset of transcription factors determines competitive fitness, and second, that the outcome of cell competition is determined by the relative cellular metabolic status.